2023
DOI: 10.1136/bmjopen-2022-064758
|View full text |Cite
|
Sign up to set email alerts
|

Mind-body exercise interventions for prevention of post-traumatic stress disorder in trauma-exposed populations: a systematic review and meta-analysis

Abstract: ObjectiveMind-body exercise (MBE) interventions, such as yoga, are increasingly recognised as an adjunct treatment for trauma-related mental disorders but less is known about their efficacy as a preventative intervention. We aimed to systematically review if, and what type of, MBE interventions are effective at preventing the development of post-traumatic stress disorder (PTSD) or acute stress disorder (ASD) in trauma-exposed populations.DesignSystematic review and meta-analysis.MethodsA systematic search of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Our findings support previous trials on MBE interventions for trauma-exposed populations on posttraumatic stress symptoms (Kelly & Garland, 2016; Saban et al, 2022) and the small effect size at postintervention is consistent with a previous review on MBE for preventing the development of PTSD (Tan et al, 2023). While we did not find any differential effects on individuals with full PTSD, our significant findings for individuals with subthreshold PTSD have important implications around early interventions and possible selective prevention of PTSD (Fink et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings support previous trials on MBE interventions for trauma-exposed populations on posttraumatic stress symptoms (Kelly & Garland, 2016; Saban et al, 2022) and the small effect size at postintervention is consistent with a previous review on MBE for preventing the development of PTSD (Tan et al, 2023). While we did not find any differential effects on individuals with full PTSD, our significant findings for individuals with subthreshold PTSD have important implications around early interventions and possible selective prevention of PTSD (Fink et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Moderate effects have been found for yoga and meditation in improving PTSD symptoms among Veterans (Gallegos et al, 2017), another high-risk cohort with similar occupational characteristics to first responders. Furthermore, a meta-analysis found potential evidence for MBE interventions in preventing the development of PTSD in the short term (Tan et al, 2023). Despite these promising findings, evidence on MBE interventions is limited by the small number of high-quality studies (Cramer et al, 2018; Gallegos et al, 2017; Tan et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing interventions, such as psychological first aid (Brymer et al, 2006), could not be evaluated for inclusion because no randomized controlled trials of these approaches were identified in the review for the CPG; however, other researchers have concluded that the evidence that this approach is effective in preventing PTSD is weak (Hermosilla et al, 2023). In the interim, clinicians should strive to address basic needs (e.g., shelter, food), identify individuals at high risk of adverse outcomes, and support wellness (e.g., community support, exercise; Magruder et al, 2017;Tan et al, 2023). Module A (p. 26) of the clinical algorithm outlines strategies for identifying and managing ASR and ASD.…”
Section: Acute Stress Reaction (Asr) and Asdmentioning
confidence: 99%